APPLICATION OF MAMDANI FUZZY METHOD TO PREDICT THE AMOUNT OF PINE RESIN PRODUCTION - Fairus, Fairus; Putri, Sonia Anisa; Muliani, Fitra (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
PT. Inhutani IV Aceh District needs to plan the right production in order to achieve maximum profit. Therefore, the company needs to develop a system that can predict the amount of pine resin that can be produced. This study uses data from PT. Inhutani IV Aceh District which is engaged in the production of raw pine resin. This study uses the mamdani fuzzy method to predict the amount of latex production based on demand data, supply data and latex production data per month in 2019-2020. Based on the results of calculations that have been carried out, with the input variable demand in January 2021 of 91,404 kg and supply in December 2020 of 71,466 kg, with the fuzzy mamdani method, the prediction results of the pine resin that the company can produce is 191,763 kg in January 2021 and based on the results of calculations using the MAPE accuracy measure, the fuzzy mamdani method has a MAPE value of 45.69 % so it can be concluded that the mamdani fuzzy method is pretty good for predicting the production of pine resin at PT. Inhutani IV Aceh District.